Pengaruh Media Booklet dan Lembar Balik terhadap Pengetahuan, Sikap dan Keterampilan Siswa tentang Covid-19 - Rini Patroni; Evron Veriza (Faletehan Health Journal, 2025)
The best way to prevent COVID-19 disease is to break the chain of the spread of the virus through isolation, early detection and preventive protocols. These efforts must be disseminated to the community, including junior high school students and can be done using the media of booklet and flipbook. The purpose of this study was to find out the difference of booklet and flipbook media influence on the knowledge, attitudes and skills of junior high school students about COVID-19. This study used a pre-experimental method with a research design of one group pretest-posttest with control group. The research was conducted in 2 public junior high schools in Bengkulu City with a sample of 30 students in the treatment group and 30 students in the control group. The results of the research explained that the average knowledge of students who used booklet media was 2.00, the average attitude was 1.90 and skills were 1.90. Meanwhile, the average knowledge of the control group with the media of the flipbook was 1.83, attitude was 1.90 and skill was 1.80. Booklet media is more effective in improving students' knowledge, attitudes and skills about COVID-19 than flipbook media.